Assessment of Domestic Wastewaters as Potential Growth Media for Chlorella vulgaris and Haematococcus pluvialis - Tan Y.H.; Chai M.K.; Ooi Y.K.; Wong L.S. (Universiti Putra Malaysia Press, 2023)
Domestic wastewater contains chemical compounds that can be used as nutrients for microalgae. Removing these chemical compounds from wastewater by microalgae might help in reducing the operation cost of wastewater management while minimizing the cultivation cost for large-scale microalgae metabolite production. In this study, domestic wastewater collected from Indah Water Konsortium (IWK), Kuala Lumpur, Malaysia, was assessed as growth media for two types of microalgae, namely Chlorella vulgaris and Haematococcus pluvialis. The biomass growth and nutrient removal efficiency of total nitrogen (TN), total phosphorus (TP), and total ammonia (TAN) in different concentrations of diluted wastewater were measured. The results showed that biomass concentration (0.227 g/L), biomass productivity (0.029 g/L/day), and specific growth rate (0,284 d-1) yielded by C. vulgaris in 14 days of 80% wastewater were comparable to those microalgae grew in standard Bolds Basal medium (BBM). Besides, C. vulgaris grew in 50% wastewater to remove TN, TP, and TAN with the highest removal efficiency (>88%). For H. pluvialis, the biomass concentration in all wastewater concentrations was lower than BBM. The removal efficiencies of TN and TP were lower than 55%, but more than 80% for removal efficiency of TAN in 50% and 80% wastewater. Hence, C. vulgaris has better growth performance and nutrient removal efficiency than H. pluvialis. These findings indicated that IWK domestic wastewater could be used as growth media for microalgae, especially C. vulgaris. Universiti Putra Malaysia Press.